Kryteria wyboru - kredyt czy leasing - Wolak-Tuzimek, Anna (Credit of Leasing - Discretion Criterion, 2006)
The choice of financial sources for enterprise activity is a strategic decision and depends on many [ factors. The paper presents both external and internal factors influencing the proper choice of financing forms. Taking the credit and leasing as an example, the criteria used while choosing one of the above factors are presented. The factors which enable to compare the credit and leasing offer as well as to take the optimum decision concerning the choice of financial sources of an enterprise are shown.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 716-725